Perfil do trabalhador da construção civil da região metropolitana de Belém - PA - SOUZA, Lourdes Oliveira e (Universidade Federal do Pará, 2018)
The civil construction has great importance in development of a region, creating several workstations that, when well connected, generate the final product with quality. Its labour is generally low-qualified in study terms, discriminated and devalued. Besides, we also highlighted the high accident rates related to labor activity and their affects affect not only the workers, but their families and the company. In order to know that labour, this present study had as main objective to trace the worker’s profile of the civil construction in the Belém Metropolitan Region (PA), through a case study with applying a questionnaire, divided in 3 important topics: personal, socioeconomic and professional knowledge, applied to 450 workers in several construct sites of 12 companies of civil construction’s industry. As main results, obtained that 32,0% have completed high school, 86,0% receive up 2 minimum wage, 32,9% are at civil construction’s industry between 2 and 5 years, 69,0% have own houses and 61,8% feel pains, mainly in the backs, lumbar and arms. This research will serve as an incentive for the realization of new studies in qualification and workplace safety, associated to satisfaction and improving people's living conditions of these workers, increasing in productivity and reduction of costs for the company.